Detection of Phosphorylated Insulin Receptor in Colorectal Adenoma and Adenocarcinoma: Implications for Prognosis and Clinical Outcome. Issue 3 (March 2015) - Abbruzzese, Claudia; Diodoro, Maria Grazia; Sperduti, Isabella; Mileo, Anna Maria; Pattaro, Giada; De Salvo, Laura; Cosimelli, Maurizio; Perrotti, Nicola; Paggi, Marco G.
<x xml:space="preserve">Abstract</x> Colorectal carcinoma remains among the most frequent causes of cancer death. Besides the well‐known genetic predisposition, a key role in colorectal adenoma and adenocarcinoma etio‐pathogenesis, mainly in sporadic cases, is played by definite risk factors, such as obesity, type 2 diabetes, insulin resistance, hyper‐insulinemia, and insulin therapy. These epidemiological data motivated us to determine, by means of immunohistochemistry, the amount of activated (phosphorylated) insulin receptor in archival samples from 22 colorectal adenoma and 117 adenocarcinoma patients, with the objective to estimate the role of this factor in colorectal epithelium transformation and cancer progression. Statistical analysis of the results clearly showed that positive staining for phosphorylated insulin receptor was significantly more frequent in adenomas than adenocarcinomas (P < 0.0001) and, within the adenocarcinoma cohort, it was more frequent in low‐grade tumors (P = 0.005). In adenomas, staining was exclusively cytoplasmic, while in adenocarcinomas it was cytoplasmic and/or nuclear (P < 0.0001). Interestingly, disease‐free survival in colorectal adenocarcinoma patients pointed out a significantly better prognosis for those bearing a positive staining for phosphorylated insulin receptor (P = 0.02). From these data, we can argue that activated insulin receptor plays a fundamental role at the early stages of tumorigenesis, where late stages could be characterized by a shift toward more active oncogenic drivers. Determining the amount of phosphorylated insulin receptor could thus represent a novel prognostic/predictive tool in colorectal adenocarcinoma patients. J. Cell. Physiol. 230: 562–567, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company